Screening for the main triterpenic acids in Centella asiatica samples from North and South of Vietnam - Quynh Nhu, Vo Thi; Phuong Thao, Tran Thi; Sung, Tran Van; Loc, Tran Van (Vietnam Journal of Chemistry, 2016)
The optimal conditions for extraction, hydrolyzation and quantitative determination of the total amounts of two main triterpene acids, asiatic acid, and madecassic acid in Centella asiatica by HPLC and column chromatography are described. Using this method the asiatic acid and madecassic acid content of three Centella asiatica samples collected in Sontay City, Namdinh province, and in Ho Chi Minh City have been screened. The result showed that the contents of both triterpenic acids are higher in Sontay sample and in each sample the content of madecassic acid is higher than that of asiatic acid. Keywords. Centella asiatica, asiatic acid, madecassic acid, quantification.